2012
DOI: 10.1183/09031936.00092211
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation in children and young adults: a 20-year single-centre experience

Abstract: Lung transplantation in adults is an accepted therapeutic option, whereas there is ongoing debate on its positive impact on survival in children. We report our experience of the first 20 yrs of paediatric lung transplantation at a single centre in Austria.Patient survival, organ survival and freedom from bronchiolitis obliterans were estimated by Kaplan-Meier curves. Pre-and post-transplant parameters were assessed and their influence on patient and organ survival evaluated by univariate tests and stepwise mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Since the first heart-lung transplant for CF performed in 1984, there have been significant advances in the surgical technique (i.e., en bloc double-lung transplants, bilateral sequential lung transplants) and the post-transplantation medical management, and overall post-transplant survival has improved. 3 Several published reports described single-center experiences [4][5][6] ; however, population-based studies characterizing health outcomes after lung transplant in CF are scarce. Thabut et al 7 used United Network for Organ Sharing data (2005)(2006)(2007)(2008)(2009)) and reported the 1-year and 3-year posttransplant survival for 454 patients with CF in the United States was 88.4% and 67.8%, respectively.…”
mentioning
confidence: 99%
“…Since the first heart-lung transplant for CF performed in 1984, there have been significant advances in the surgical technique (i.e., en bloc double-lung transplants, bilateral sequential lung transplants) and the post-transplantation medical management, and overall post-transplant survival has improved. 3 Several published reports described single-center experiences [4][5][6] ; however, population-based studies characterizing health outcomes after lung transplant in CF are scarce. Thabut et al 7 used United Network for Organ Sharing data (2005)(2006)(2007)(2008)(2009)) and reported the 1-year and 3-year posttransplant survival for 454 patients with CF in the United States was 88.4% and 67.8%, respectively.…”
mentioning
confidence: 99%
“…Our analysis demonstrated a significant decrease of 16% in FEV1 in our cohort after starting chronic opioid therapy, which suggests acceleration of post‐transplant PFT decline . Bronchiolitis Obliterans Syndrome is clinically suggested after an irreversible drop in FEV1 of 20% or more .…”
Section: Discussionmentioning
confidence: 50%
“…Bronchiolitis Obliterans Syndrome is clinically suggested after an irreversible drop in FEV1 of 20% or more . The decline in FEV1 associated with chronic opioid use is especially concerning as previous studies have shown that FEV1 peaks between 3 to 12 months after LTx, and decreases with episodes of rejection or infection with 50% of LTx recipients developing chronic lung allograft dysfunction by 5‐year post‐transplant . Moreover, chronic opioid use was associated with an increase in mortality hazard in our cohort conditional on survival to 1‐year post‐LTx.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations